Implementation Of New Public Management Principles In Improving Passport Services At The Class I Immigration Office TPI Denpasar - Itu, Maria Yuliana; Dewi, Ni Luh Yulyana (Pasundan Social Science Development, 2024)
The purpose of this study is to determine the Implementation of the New Public Management Principle in Improving Passport Services at the Class I TPI Denpasar Immigration Office. By using a qualitative descriptive method, the researcher directly went to the research location and conducted interviews with parties who knew how the Implementation of the New Public Management Principle in Improving Passport Services at the Class I TPI Denpasar Immigration Office, as well as external parties, namely the community as passport applicants. This aims to obtain accurate information regarding the Implementation of the New Public Management Principle in Improving Passport Services at the Class I TPI Denpasar Immigration Office. The results of the study indicate that the implementation of the New Public Management (NPM) principle in passport services at the Class I TPI Denpasar Immigration Office based on the principles that are the characteristics of NPM according to Christopher Hood is not all optimal and still needs improvement to be more efficient in passport services at the Class I TPI Denpasar Immigration Office.